Ziran-Wuwei philosophy and practices : a Daoist epistemological framework towards education - Hu, Xiaoting (2024)
As the founding text of Daoism, Dao De Jing has in the course of its thousand-year history powerfully influenced many dimensions of the political, social and philosophical traditions both in China and beyond. In this thesis, I delve into the central Daoist notions of Ziran-Wuwei (自然 无为 “spontaneity” and “non-action”) and explore the epistemological differences they inspire in our approaches towards education. Using a hermeneutic text analysis of Daoist texts and a Critical Theory framework to explore Daoist implications in education, I seek to introduce a new imagination of approaches to education - rooted in the century-old Daoist tradition - that challenges the dominated ways of thinking and practices in the education. I argue for a Ziran-wuwei education that aligns with the operation of Dao; it highlights the development of a state of being in which one engages in spontaneous ways with the surrounding environment of relatedness with minimum impositional actions and normative paradigms of thinking.